2018
DOI: 10.5115/acb.2018.51.3.158
|View full text |Cite
|
Sign up to set email alerts
|

From dentistry students' points of view: do anatomy classes we took actually boost our learning during clinic?

Abstract: The aim of medical education is to teach the essence of practical skills alongside with the theoretical knowledge. Teaching anatomy, as the center of medical education, should be leading to use this knowledge as a skill during clinical period. According to the rising numbers of dentistry faculties' experiences, inappropriate education results in misguidance during clinic. Thus, this study was conducted to find about the pre-clinical and clinical dentistry students' points of view on the helpfulness of anatomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…This suggested that the change of teacher between the first and the second sessions, even though reducing the bias due to different teaching performances among teaching methods, may still have acted as a cofounding factor between sessions, in addition to the use of dry skulls. Accordingly, teacher's characteristics have been reported to influence the perception of learning of dental students (Anarkooli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the change of teacher between the first and the second sessions, even though reducing the bias due to different teaching performances among teaching methods, may still have acted as a cofounding factor between sessions, in addition to the use of dry skulls. Accordingly, teacher's characteristics have been reported to influence the perception of learning of dental students (Anarkooli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%